Comparative Study of Toponyms In English and Uzbek Languages - kizi, Usmonova (Academicia Globe: Inderscience Research, 2025)
The article substantiates the idea that the nature of place names is influenced by the structure of the language, its imagery, grammatical structure, interaction with other languages, as well as the natural environment in which native speakers live. The style of thinking, perception of the world through images and representations are reflected in the names of the geographical environment, their preservation and use in everyday life, as well as in artistic practice. The use of place names, their transfer from one language to another, and the nature of the distortions that occur depend on the group and language family to which they belong. This article examines the relationship of toponymy with linguistics, history, and geography. The study is devoted to the analysis of the role of toponyms not only in the designation of geographical objects, but also in the transmission of cultural, historical and linguistic heritage of peoples.